2008
DOI: 10.1177/0091270008322911
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers and Coagulation Tests for Assessing the Biosimilarity of a Generic Low‐Molecular‐Weight Heparin: Results of a Study in Healthy Subjects With Enoxaparin

Abstract: Low-molecular-weight heparins (LMWHs) differ considerably in their influence on clotting tests and release of tissue factor pathway inhibitor (TFPI). Biosimilarity therefore becomes an issue when generic forms of LMWHs are developed. So far, no bioequivalence study with a generic LMWH has been reported. A generic enoxaparin (test) was compared with the originator (reference) in 20 volunteers after single-dose subcutaneous administration (40 mg enoxaparin sodium, 4000 IU/mL anti-factor Xa (anti-FXa; activity). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 21 publications
1
31
0
Order By: Relevance
“…Most are Phase I cross over studies in healthy volunteers, with subcutaneous single doses of 100, 400 and 600 mg enoxaparin or comparator. The general conclusions from these studies is that they are bioequivalent . One study has the focus on immunogenicity of a product from Brazil compared to the originator enoxaparin.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most are Phase I cross over studies in healthy volunteers, with subcutaneous single doses of 100, 400 and 600 mg enoxaparin or comparator. The general conclusions from these studies is that they are bioequivalent . One study has the focus on immunogenicity of a product from Brazil compared to the originator enoxaparin.…”
Section: Methodsmentioning
confidence: 99%
“…The is that they are bioequivalent. [25][26][27] One study has the focus on immunogenicity of a product from Brazil compared to the originator enoxaparin. There was a difference in AHPF4 antibodies for the biosimilar, but the authors made no conclusions what should be the consequence of this finding.…”
Section: Clinical Aspects Of Lmwhs With Special Attention For Hitmentioning
confidence: 99%
“…One in vitro study found structural variability but similar biological activities between brand and generic versions [27]. The remaining studies found that bioequivalence was met for the generic version [28][29][30].…”
Section: Studies Of Non-fda-approved Generic Versionsmentioning
confidence: 99%
“…LMWH have a characteristic molecular weight profile and biological activity in terms of anti‐FXa and anti‐FIIa potency, but cannot be physically detected in vivo as a single chemical entity . Instead, the pharmacokinetic (PK) properties of LMWH, including bioavailability, absorption and elimination, are determined using pharmacodynamic (PD) surrogate markers, such as circulating anti‐FXa and anti‐FIIa activity . Other PD tests, including the ratio of anti‐FXa to anti‐FIIa activity, and assays for tissue factor pathway inhibitor (TFPI), are indirect measures of the in vivo activity of LMWH .…”
Section: Low Molecular Weight Heparins: Challenges In Chemical Characmentioning
confidence: 99%
“…Instead, the pharmacokinetic (PK) properties of LMWH, including bioavailability, absorption and elimination, are determined using pharmacodynamic (PD) surrogate markers, such as circulating anti‐FXa and anti‐FIIa activity . Other PD tests, including the ratio of anti‐FXa to anti‐FIIa activity, and assays for tissue factor pathway inhibitor (TFPI), are indirect measures of the in vivo activity of LMWH . These measurements are directly influenced by the amount of LMWH present in the plasma sample, although they may not necessarily reflect its full biological activity in vivo , or accurately reflect its clinical efficacy …”
Section: Low Molecular Weight Heparins: Challenges In Chemical Characmentioning
confidence: 99%